Evaluation of Plaque Stability of Advanced Atherosclerotic Lesions in Apo E-Deficient Mice after Treatment with the Oral Factor Xa Inhibitor Rivaroxaban - Qianxing Zhou; Florian Bea; Michael Preusch; Hongjie Wang; Berend Isermann; Khurrum Shahzad; Hugo A. Katus; Erwin Blessing (Mediators of Inflammation)
Aim. Thrombin not only plays a central role in thrombus formation and platelet activation, but also in induction of inflammatory processes. Activated factor X (FXa) is traditionally known as an important player in the coagulation cascade responsible for thrombin generation. We assessed the hypothesis that rivaroxaban, a direct FXa inhibitor, attenuates plaque progression and promotes stability of advanced atherosclerotic lesions in an in vivo model. Methods and Results. Rivaroxaban (1 or 5 mg/kg body weight/day) or standard chow diet was administered for 26 weeks to apolipoprotein E-deficient mice (n=20 per group) with already established atherosclerotic lesions. There was a nonsignificant reduction of lesion progression in the high-concentration group, compared to control mice. FXa inhibition with 5 mg Rivaroxaban/kg/day resulted in increased thickness of the protective fibrous caps (12.3±3.8 μm versus 10.1±2.7 μm; P<.05), as well as in fewer medial erosions and fewer lateral xanthomas, indicating plaque stabilizing properties. Real time-PCR from thoracic aortas revealed that rivaroxaban (5 mg/kg/day) treatment reduced mRNA expression of inflammatory mediators, such of IL-6, TNF-α, MCP-1, and Egr-1 (P<.05). Conclusions. Chronic administration of rivaroxaban does not affect lesion progression but downregulates expression of inflammatory mediators and promotes lesion stability in apolipoprotein E-deficient mice.